第一个=后面是切割化弦,然后把分母全化成sinθ-cosθ ,通分就行了啦
sin^2θ/sinθ-cosθ + cosθ/1-tanθ = sin^2θ/sinθ-cosθ + cosθ/1-(
2个回答
相关问题
-
求证 (sinθ+cosθ-1)(sinθ-cosθ+1)) /sin2θ=tanθ/2
-
2sinθ-cosθ=1 (sinθ+cosθ+1)/(sinθ-cosθ+1)
-
:求证:(1-2sinθcosθ)/(cos2θ-sin2θ)=(cos2θ-sin2θ)/(1+2sinθcosθ).
-
求证:(1+cosθ+cosθ/2) /(sinθ+sinθ/2)=sinθ/1-cosθ
-
若tanθ=1/2则(cosθ+sinθ/cosθ-sinθ)
-
求证:(1-tanθ)/(1+tanθ)=(1-2sinθcosθ)/(cos2θ-sin2θ)
-
求证:2(cos θ -sin θ )/(1+sinθ +cosθ)=tan(∏/4- θ /2)-tan(θ /2)
-
求证 【sinθ(1+sinθ)+cosθ(1+cosθ)】×【sinθ(1-sinθ)+cosθ(1-cosθ)】=s
-
求证:tanθ*sinθ/tanθ-sinθ=1+cosθ/sinθ
-
求证:sin2θ+sinθ/2cos2θ+2sin^2θ+cosθ=tanθ